Pemanfaatan Cerita Pendek Sebagai Media Pendidikan Karakter Siswa - Setiawan, Arief Wahyu; Ningsih, Tutuk (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
In the world of education, there are cognitive aspects and affective aspects, both of which are important aspects to achieve learning objectives. The affective aspect needs attention because it is related to the formation of student character. Various negative phenomena that have been carried out or experienced by students lately have made it clear that character education is increasingly important for students. Character education activities can be applied in almost all subjects, especially the Indonesian language subject. Various literary subjects can be used by teachers to transform noble character values to students. This study uses a qualitative descriptive method of literature review research. From the research, it can be concluded that literature is very effectively used in character building in students. One of the literary works that have been included in the Indonesian language subject education curriculum is a short story. Using short story media, teachers can transform the character values contained in short stories to students, which are then expected to be applied to everyday life.